Guidebooks and Rankings: The Value of Optional External Reporting. Issue 166 (January 2016) - Carpenter‐Hubin, Julia; Crisan‐Vandeborne, Liana
Abstract : This chapter details the benefits and costs of participating in optional external reporting and considers how best to determine which reports represent the best use of time and resources.